Metoclopramide-Induced Acute Dystonia: Data From a Pediatric Emergency Unit. Issue 9 (September 2021) - Yarar, Coskun; Yakut, Ayten; Carman, Kursat Bora; Sahin, Sabiha; Kocak, Ozan; Ozkan, Serhat; Bal, Cengiz
Abstract : Objectives: Metoclopramide is a commonly used medication in pediatric practice, and dystonia is a common adverse effect of it. The present study aims to evaluate the clinical characteristics of metoclopramide-induced acute dystonic reactions (MIADRs) in pediatric patients admitted to the pediatric emergency unit. Methods: Twenty-eight patients were admitted with MIADRs between June 2004 and April 2016; they were enrolled into the study retrospectively. Results: The study group was composed of 13 females and 15 males with the mean ± SD age of the females higher than that of the males, 12.3 ± 4.5 and 7.8 ± 4.3 years, respectively. Only 9 (32.1%) of the patients were diagnosed as MIADRs at the time of admission. Seventeen patients (60.7%) received over the recommended daily dose of metoclopramide. Dystonia was focal in most of the patients, with the most affected parts consisting of the neck, eyes, and orolingual regions. In 9 of the patients, the dystonia was episodic in nature. Pharmacological treatment was used for 18 patients. No patients died, and none suffered long-term injury related to MIADRs. Conclusions: Metoclopramide administration may be associated with the occurrence of acute dystonic reaction. Metoclopramide-induced acute dystonic reactions may be misdiagnosed, so detailed medical history gathering and a high index of suspicion are warranted. Our data suggest that MIADRs may be dose related and that there may be age- and sex-related differences in the epidemiology of MIADRs.